Alzheimer‐Related Cerebrovascular Disease in Down Syndrome. Issue 6 (9th October 2020) - Lao, Patrick J.; Gutierrez, José; Keator, David; Rizvi, Batool; Banerjee, Arit; Igwe, Kay C.; Laing, Krystal K.; Sathishkumar, Mithra; Moni, Fahmida; Andrews, Howard; Krinsky‐McHale, Sharon; Head, Elizabeth; et al.
Abstract : Objective: Adults with Down syndrome (DS) develop Alzheimer disease (AD) pathology by their 5th decade. Compared with the general population, traditional vascular risks in adults with DS are rare, allowing examination of cerebrovascular disease in this population and insight into its role in AD without the confound of vascular risk factors. We examined in vivo magnetic resonance imaging (MRI)‐based biomarkers of cerebrovascular pathology in adults with DS, and determined their cross‐sectional relationship with age, beta‐amyloid pathology, and mild cognitive impairment or clinical AD diagnostic status. Methods: Participants from the Biomarkers of Alzheimer's Disease in Down Syndrome study (n = 138, 50 ± 7 years, 39% women) with MRI data and a subset (n = 90) with amyloid positron emission tomography (PET) were included. We derived MRI‐based biomarkers of cerebrovascular pathology, including white matter hyperintensities (WMH), infarcts, cerebral microbleeds, and enlarged perivascular spaces (PVS), as well as PET‐based biomarkers of amyloid burden. Participants were characterized as cognitively stable (CS), mild cognitive impairment–DS (MCI‐DS), possible AD dementia, or definite AD dementia based on in‐depth assessments of cognition, function, and health status. Results: There were detectable WMH, enlarged PVS, infarcts, and microbleeds as early as the 5th decade of life. There was a monotonic increase in WMH volume, enlarged PVS, and presence of infarcts across diagnostic groups (CS < MCI‐DS < possible AD dementia < definite AD dementia). Higher amyloid burden was associated with a higher likelihood of an infarct. Interpretation: The findings highlight the prevalence of cerebrovascular disease in adults with DS and add to a growing body of evidence that implicates cerebrovascular disease as a core feature of AD and not simply a comorbidity. ANN NEUROL 2020;88:1165–1177